Is Crisis Intervention Useful or Not? An Attempt To Determine The Effectivness Of Crisis Inteventions - Bajs, Martina; Bugan, Anita; Stamać, Zrinka; Arambašić, Lidija; Jelić, Margareta (2003)
This study represents an attempt to evaluate the effectiveness of crisis intervention in lessening the severity of consequences of traumatic experience caused by a critical incident. In order to determine the effectiveness of the procedure, a questionnaire was used (designed for this purpose in 2000 by psychologists from Society for Psychological Assistance: Arambašić, Profaca, Starc) that has 11 questions designed to be answered by people to whom an intervention was provided approximately 3 months earlier. One of the respondent's task was to asses his/her emotions, behavior and looking for support as reactions to the critical event in three time periods: at the time it occurred, 2 weeks later and on the day of the evaluation. Respondents were also asked whether they considered the intervention harmful, non-efficient (neutral), useful or extremely useful, and asked for their present view of the critical event. Evaluation data were obtained from N = 223 adults and young people who were involved in three crisis interventions after three critical events: suicide (16 years old girl), rifle shooting in the classroom (15 years old boy), murder of social worker in the office of the Center for Social Welfare (38 years old social worker's client). All three crisis interventions were carried out by professionals from the Society for Psychological Assistance, Zagreb, Croatia. Both qualitative and quantitative data were analyzed for frequencies and core categories. Results show that 46% of the clients find the intervention useful. There is a low rate of absence/sick leaves caused by the event (6%), and a high rate of acceptance and reconciling with the critical event (31%). Even though the results cannot be considered as "pure" intervention outcomes, they are a valuable source of ideas for future improvement of the evaluation of the effectiveness of crisis intervention procedures.
Projekt MZOS
ENG